Pengaruh Lingkungan Keluarga Dan Lingkungan Sekolah Terhadap Peningkatan Spiritual Siswa Kelas VII Mts Maulana Ishaq Kemantren Paciran Lamongan - Zulkifli; Mustadi; Ahmad Thoyyib Mas’udi (Pascasarjana Universitas Qomaruddin, 2026)
This study aims to examine the influence of the family environment and the school environment on the improvement of students’ spirituality in Grade VII at MTs Maulana Ishaq Kemantren Paciran Lamongan. This research employed a quantitative approach with a correlational research design. The population of the study consisted of all students of MTs Maulana Ishaq Kemantren Paciran Lamongan, with the sample comprising Grade VII students selected using a sampling technique appropriate to the research objectives. Data were collected through questionnaires, observations, and documentation. The collected data were analyzed using statistical analysis with the assistance of SPSS software. The results indicate that, partially, the family environment has a significant effect on students’ spirituality, with a correlation coefficient of 0.901, which falls into the very high correlation category. The school environment also shows a significant influence on students’ spirituality, with a correlation coefficient of 0.901 and significance values exceeding the r-table values at both the 5% and 1% significance levels. Simultaneously, the family and school environments have a positive and significant effect on students’ spirituality, with a correlation coefficient of 0.906. These findings demonstrate that both family and school environments play an important role in enhancing students’ spirituality.